A systematic review of actions aimed at university students with ADHD - Álvarez-Godos, María; Ferreira, Camino; Vieira, María-José (Frontiers in Psychology, 2023)
University students with Attention Deficit Hyperactivity Disorder (ADHD) need to have a range of actions at their disposal that are tailored to their needs. The aim of this study is to analyse the actions of support for university students with ADHD by means of a systematic review of ERIC, WOS, and Scopus from 2017 to 2022, following the PICOC and PRISMA guidelines. A sample of 24 studies are analysed through the MAXQDA 2022 software. The results show two types of studies, on the one hand, supporting actions offered directly by universities to their students and, on the other, intervention programs from which university students have benefit but outside the university settings. Concerning the first type, universities mainly offer accommodations linked to exams, tutoring and online courses adapted to ADHD students. About the second type, programmes focused on cognitive-behavioural therapy, coaching and mindfulness have proven to be useful with ADHD university students. In this sense, further research is needed to analyze the viability of including these intervention programs for ADHD students at universities.